Peningkatan Edukasi, Kesehatan, dan Ekonomi Masyarakat Desa Ciantra Melalui Lomba, Penyuluhan, Cek Kesehatan dan Bazar UMKM - Army Cahya Putra Rustamaji; Aly Mulkan Arifuddin; Firli Fahsyaroni; Muhamad Nurul Ainil Yaqin; Nur Hanifah (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to improve public health and economic education in Ciantra Village through stunting counseling programs, health checks, and MSME development. The methods used include counseling at Posyandu to increase awareness about stunting and the importance of routine health checks, as well as MSME bazaars accompanied by marketing training to strengthen the local economy. The results of the study showed an increase in public understanding of stunting prevention and early detection of health problems, as well as an increase in sales of MSME products after rebranding. This program is not only successful in overcoming existing health and economic problems, but also strengthens the status of Ciantra Village as an independent village. The implementation of this program can be a model for other villages in an effort to achieve community independence and welfare.